A Dynamically Hybrid Crosslinked Elastomer for Room‐Temperature Recyclable Flexible Electronic Devices. (14th September 2021) - Guo, Yifan; Yang, Lei; Zhang, Luzhi; Chen, Shuo; Sun, Lijie; Gu, Shijia; You, Zhengwei
Abstract: The rapid development of flexible electronics has resulted in serious pollution in the form of electronic waste. Accordingly, recyclability is highly desirable for these devices, but this remains a significant challenge. A dynamically hybrid crosslinked polyurethane (FPU) elastomer is designed in this study to address this challenge. Distinctive Diels–Alder adducts with suitable dissociation and reassociation dynamics are designed as crosslinking units to provide an efficient time frame for recycling. FPU is maintained in a state with a low crosslinking density after heating at 120 °C for 5 min. FPU‐based electronics can therefore be dissolved in chloroform under ambient conditions to separate the electronic components and polymers for the refabrication of new electronic devices. This is the first reported thermoset elastomer that can be completely recycled at room temperature without chemical treatment to decompose the polymer chain. The design concept is applied by demonstrating the fabrication by recycling of different FPU‐based flexible electronic devices: position sensor, flexible keyboard, and motion sensor. Furthermore, the FPU has many advantages as a material for flexible electronics in terms of its biomimetic mechanical properties, room‐temperature self‐healing, and facile processability. This study provides promising new design principles to develop materials for promoting sustainable flexible electronics. Abstract : Distinctive Diels–Alder adducts with suitable dissociation and reassociation dynamics are designed as crosslinking units to enable controllable recycling of the resultant elastomer at room temperature without the need for chemical treatment to decompose the polymer chains. Furthermore, the elastomer has other advantages for electronics as well including biomimetic mechanical properties, room‐temperature self‐healing, and facile processability.